Epitope-Specific Antibody Responses to a Plasmodium falciparum Subunit Vaccine Target in a Malaria-Endemic Population. (29th September 2020) - Friedman-Klabanoff, DeAnna J; Travassos, Mark A; Ifeonu, Olukemi O; Agrawal, Sonia; Ouattara, Amed; Pike, Andrew; Bailey, Jason A; Adams, Matthew; Coulibaly, Drissa; Lyke, Kirsten E; Laurens, Matthew B; Takala-Harrison, Shannon; et al.
Abstract: Circumsporozoite protein (CSP) coats the Plasmodium falciparum sporozoite surface and is a major malaria subunit vaccine target. We measured epitope-specific reactivity to field-derived CSP haplotypes in serum samples from Malian adults and children on a custom peptide microarray. Compared to children, adults showed greater antibody responses and responses to more variants in regions proximal to and within the central repeat region. Children acquired short-lived immunity to an epitope proximal to the central repeat region but not to the central repeat region itself. This approach has the potential to differentiate immunodominant from protective epitope-specific responses when combined with longitudinal infection data. Abstract : On a custom peptide microarray that measured naturally acquired, epitope-specific antibody reactivity to field-derived Plasmodium falciparum circumsporozoite protein haplotypes, Malian adult sera had immunoglobulin G (IgG) antibodies to the Region 1-NANP junction and children had short-lived IgG responses to the same region.